PENGARUH PENAMBAHAN CACO3 DARI LIMBAH KULIT TELUR DAN WAKTU PENGADUKAN PADA PEMBUATAN ALUMINIUM FOAM MENGGUNAKAN METODE MELT ROUTE - Ikhsan Ekariadi; Yeni Muriani Zulaida; Suryana Suryana (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2023)
Aluminum is a lightweight material that has good corrosion resistance and electrical conductivity. It can be used for making aluminum foam. One of the methods for making aluminum foam is the melt route method. Making aluminum foam using the melt route process, is called melting aluminum metal, adding foaming agent, and stirring. This study aims to determine the effect of adding CaCO3 from eggshells and stirring time on the foaming ability of aluminum foam. The characteristics that will be observed include the type of aluminum foam, height, pore size, density, porosity, and compressive strength. This research used the melt route method with adding variations in the mass composition of CaCO3 is 4, 5, and 6 wt% on smelted aluminum with stirring times of 30, 45, and 60 seconds. The process is carried out by heating aluminum to 760 Â°C and adding Al2O3 as a viscosity modifier then adding variations in the mass composition of CaCO3 and stirring with a variation of stirring time. The results show that the highest aluminum foam gets a value of 75 mm. The pore sizes of aluminum foam are obtained ranged from 0.287 to 1.109 mm. The optimal value obtained from the addition of CaCO3 with a mass composition of 4 wt% with a stirring time of 45 seconds, has a density value of 0.388 g/cm3, a porosity percentage of 85.848%, and a compressive strength of 1.777 MPa.